Key genes involved in the immune response are generally not associated with intraprostatic inflammation in men without a prostate cancer diagnosis: Results from the prostate cancer prevention trial. Issue 6 (15th January 2016) - Winchester, Danyelle A.; Gurel, Bora; Till, Cathee; Goodman, Phyllis J.; Tangen, Catherine M.; Santella, Regina M.; Johnson‐Pais, Teresa L.; Leach, Robin J.; Thompson, Ian M.; Xu, Jianfeng; Zheng, S. Lilly; Lucia, M. Scott; et al.
Abstract : BACKGROUND: We previously reported that both intraprostatic inflammation and SNPs in genes involved in the immune response are associated with prostate cancer risk and disease grade. In the present study, we evaluated the association between these SNPs and intraprostatic inflammation in men without a prostate cancer diagnosis. METHODS: Included in this cross‐sectional study were 205 white controls from a case‐control study nested in the placebo arm of the Prostate Cancer Prevention Trial. We analyzed inflammation data from the review of H&E‐stained prostate tissue sections from biopsies performed per protocol at the end of the trial irrespective of clinical indication, and data for 16 SNPs in key genes involved in the immune response ( IL1β, IL2, IL4, IL6, IL8, IL10, IL12 ( p40 ), IFNG, MSR1, RNASEL, TLR4, TNFA ; 7 tagSNPs in IL10 ). Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for the association between carrying at least one minor allele and having at least one biopsy core (of a mean of three reviewed) with inflammation. RESULTS: None of the SNPs evaluated was statistically significantly associated with having at least one core with inflammation. However, possible inverse associations were present for carrying the minor allele of rs2069762 (G) in IL2 (OR = 0.51, 95%CI 0.25–1.02); carrying two copies of the minor allele of rs1800871 (T) of IL10 (OR = 0.29, 95%CI 0.08–1.00); and carrying the minor allele of rs486907 (A) in RNASEL (OR = 0.52, 95%CI 0.26–1.06). After creating a genetic risk score from the three SNPs possibly associated with inflammation, the odds of inflammation increased with increasing number of risk alleles ( P ‐trend = 0.008). CONCLUSION: While our findings do not generally support a cross‐sectional link between individual SNPs in key genes involved in the immune response and intraprostatic inflammation in men without a prostate cancer diagnosis, they do suggest that some of these variants when in combination may be associated with intraprostatic inflammation in benign tissue. Prostate 76:565–574, 2016 . © 2016 Wiley Periodicals, Inc.